A FEW GOODMEN: SURNAME‐SHARING ECONOMIST COAUTHORS. (30th October 2014) - Goodman, Allen C.; Goodman, Joshua; Goodman, Lucas; Goodman, Sarena
<x xml:space="preserve">Abstract</x> We explore the phenomenon of coauthorship by economists who share a surname. Prior research has included at most three economist coauthors who share a surname. Ours is the first paper to have four economist coauthors who share a surname, as well as the first where such coauthors are unrelated by marriage, blood, or current campus. (JEL Y9)